Diels–Alder adducts with PTP1B inhibition from Morus notabilis. (January 2015) - Wang, Meng; Gao, Li-Xin; Wang, Jue; Li, Jing-Ya; Yu, Mei-Hua; Li, Jia; Hou, Ai-Jun
Graphical abstract: Eight Diels–Alder adducts and twelve known compounds were isolated from the leaves of Morus notabilis . Some of the compounds showed inhibition against PTP1B phosphatase activity in vitro . Highlights: Eight Diels–Alder adducts were isolated from Morus notabilis . Some of the Diels–Alder adducts showed inhibition against PTP1B phosphatase. Ketalized Diels–Alder adducts in this plant were previously unknown. Abstract: Eight Diels–Alder adducts, morbilisins A–H (1 –8 ), a known analogue, chalcomoracin (9 ), together with eleven known flavonoids and 2-arylbenzofurans, were isolated from the leaves of Morus notabilis . Their structures were elucidated by extensive spectroscopic analysis, including 1D, 2D NMR, MS, and ECD data. Compounds1, 5, and7 –9 showed inhibition against PTP1B phosphatase activity in vitro .